In Vivo Visualization and Monitoring of Viable Neural Stem Cells Using Noninvasive Bioluminescence Imaging in the 6-Hydroxydopamine-Induced Mouse Model of Parkinson Disease - Hyung-Jun Im; Do Won Hwang; Han Kyu Lee; Jaeho Jang; Song Lee; Hyewon Youn; Yeona Jin; Seung U. Kim; E. Edmund Kim; Yong Sik Kim; Dong Soo Lee (Molecular Imaging)
Transplantation of neural stem cells (NSCs) has been proposed as a treatment for Parkinson disease (PD). The aim of this study was to monitor the viability of transplanted NSCs expressing the enhanced luciferase gene in a mouse model of PD in vivo. The PD animal model was induced by unilateral injection of 6-hydroxydopamine (6-OHDA). The behavioral test using apomorphine-induced rotation and positron emission tomography with [ 18 F]N-(3-fluoropropyl)-2′-carbomethoxy-3′-(4-iodophenyl)nortropane ([ 18 F]FP-CIT) were conducted. HB1.F3 cells transduced with an enhanced firefly luciferase retroviral vector (F3-effLuc cells) were transplanted into the right striatum. In vivo bioluminescence imaging was repeated for 2 weeks. Four weeks after transplantation, [ 18 F]FP-CIT PET and the rotation test were repeated. All 6-OHDA-injected mice showed markedly decreased [ 18 F]FP-CIT uptake in the right striatum. Transplanted F3-effLuc cells were visualized on the right side of the brain in all mice by bioluminescence imaging. The bioluminescence intensity of the transplanted F3-effLuc cells gradually decreased until it was undetectable by 10 days. The behavioral test showed that stem cell transplantation attenuated the motor symptoms of PD. No significant change was found in [ 18 F]FP-CIT imaging after cell transplantation. We successfully established an in vivo bioluminescence imaging system for the detection of transplanted NSCs in a mouse model of PD. NSC transplantation induced behavioral improvement in PD model mice.